Generalization of Tsytovich strength conditions for soils of anisotropic structure - Baimakhan, R.B.; Baimakhan, A.R.; Abdiakhmetova, Z.M.; Seynasinova, A.A.; Baimakhanova, G.M. (Bulletin of the Karaganda University. Mathematics Series, 2019)
The problem of developing a new generalized strength (plasticity)condition is applied to soils of anisotropic, in particular a transversal - isotropic (trans - structural) structure. This condition is derived by generalizing the known Coulomb - Moore plasticity condition σc for two directions: along the layers parallel and crosswise to layers, that is, for the perpendicular directions to the layers, relative to the isotropy plane for the transtropic soil, systematized for the first time by A.K. Bugrov and A.I. Golubev. It is proposed to analyze the possibility of generalizing the conditions of plasticity (strength) in the principal stresses σ1 and σ2, as well as on the values of the critical principal stress σ1c and σ2c, proposed and developed in due time for soils of the isotropic structure N.A. Tsytovich and N.S. Bulychev. Following the approach of W. Witke, who proposed to apply such a criterion to rocks of an orthotropic structure, the formulated criterion is proposed, which allows to determine the moment of the onset of plastic destruction of anisotropic soil and the direction of its further spread from the initial point. The table contains critical values of anisotropic soil in two orthogonal directions of the coordinate axes, calculated with the help of the proposed new criterion, which allows us to solve a new class of problems of fracture mechanics.